Tunable Spin-orbit Coupling and Quantum Phase Transition in a Trapped Bose-Einstein Condensate - Zhang, Yongping (Nature Publishing Group, 2013)
Spin-orbit coupling (SOC), the intrinsic interaction between a particle spin and its motion, is responsible for various important phenomena, ranging from atomic fine structure to topological condensed matter physics. The recent experimental breakthrough on the realization of SOC for ultra-cold atoms provides a completely new platform for exploring spin-orbit coupled superfluid physics. However, the SOC strength in the experiment is not tunable. In this report, we propose a scheme for tuning the SOC strength through a fast and coherent modulation of the laser intensities. We show that the many-body interaction between atoms, together with the tunable SOC, can drive a quantum phase transition (QPT) from spin-balanced to spin-polarized ground states in a harmonic trapped Bose-Einstein condensate (BEC), which resembles the long-sought Dicke QPT. We characterize the QPT using the periods of collective oscillations of the BEC, which show pronounced peaks and damping around the quantum critical point.